Suture granuloma with hydronephrosis caused by ileostomy closure after rectal cancer surgery: a case report - Yasuhiro Takano; Koichiro Haruki; Shu Tsukihara; Tadashi Abe; Muneyuki Koyama; Daisuke Ito; Hironori Kanno; Kyonsu Son; Nobuyoshi Hanyu; Ken Eto (Surgical Case Reports, 2021)
Abstract Background Suture granuloma with hydronephrosis after abdominal surgery is extremely rare. We herein report a successfully treated case of suture granuloma with hydronephrosis caused by ileostomy closure after rectal cancer surgery. Case presentation A 63-year-old male underwent laparoscopic low anterior resection with covering ileostomy. Two months after primary operation, ileostomy closure was performed with two layered hand-sewn suture (Albert–Lembert method) using absorbable suture. In that operation, marginal blood vessels in the mesentery were ligated with silk suture. The patient had remained in remission with no evidence of tumor recurrence, however, 2 years and 5 months after primary surgery, a contrast-enhanced computed tomography (CT) scan showed a mass-forming lesion on the right external iliac artery (43 × 26 mm) and hydronephrosis. Positron emission tomography/computed tomography (PET/CT) showed a mass-forming lesion without high accumulation, which obstructed the right ureter. Recurrence could not be ruled out due to the rapid appearance of tumor and hydronephrosis in the short-term period. Thus, the patient underwent laparotomy. The tumor located in the mesentery near the anastomosis of ileostomy closure and it was strongly adherent to the retroperitoneum, which obstructed the right ureter. The adhesion between the tumor and ureter was carefully dissected and tumor resection with partial small bowel resection was then performed with preservation of the ureter using ureteral stents. Pathological examination of the tumor revealed fibrous proliferation of foreign body granuloma. In the resected tumor, sutures with foreign giant cells were found. Therefore, we diagnosed the tumor as silk suture granuloma, which was caused by the silk suture used to ligate blood vessels of the mesentery at the ileostomy closure. The patient remained well with no evidence of tumor recurrence as 5 years after the primary operation of rectal cancer. Conclusions Suture granuloma is a rare surgery-related complication in the postoperative surveillance of patients with colorectal cancer. If suture granuloma mimicking local recurrence is a differential diagnosis, it would be important to consider to avoid unnecessary extended resection.